Toughening oxide glasses through paracrystallization - Tang, Hu; Cheng, Yong; Yuan, Xiaohong; Zhang, Kai; Kurnosov, Alexander; Chen, Zhen; Xiao, Wenge; Jeppesen, Henrik S.; Etter, Martin; Liang, Tao; Zeng, Zhidan; Wang, Fei; et al. (Nature materials, 2023)
Glasses, unlike crystals, are intrinsically brittle due to the absence of microstructure-controlled toughening, creating fundamental constraints for their technological applications. Consequently, strategies for toughening glasses without compromising their other advantageous properties have been long sought after but elusive. Here we report exceptional toughening in oxide glasses via paracrystallization, using aluminosilicate glass as an example. By combining experiments and computational modelling, we demonstrate the uniform formation of crystal-like medium-range order clusters pervading the glass structure as a result of paracrystallization under high-pressure and high-temperature conditions. The paracrystalline oxide glasses display superior toughness, reaching up to 1.99 ± 0.06 MPa m 1/2 , surpassing any other reported bulk oxide glasses, to the best of our knowledge. We attribute this exceptional toughening to the excitation of multiple shear bands caused by a stress-induced inverse transformation from the paracrystalline to amorphous states, revealing plastic deformation characteristics. This discovery presents a potent strategy for designing highly damage-tolerant glass materials and emphasizes the substantial influence of atomic-level structural variation on the properties of oxide glasses. Through the approach of paracrystallization under high-pressure and high-temperature conditions, exceptional toughening has been achieved in oxide glasses by enhancing their crystal-like medium-range order structure. This discovery offers possibilities for the design of more resilient glass materials.